How Hydro Ontario Went Local: The Creation of Local Districts and the Ontario Central System - Lucas, Jack (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2014)
When Ontario Hydro was created, its task was to distribute electricity to local hydro commissions across Ontario. By the 1920s, however, it had become a local distributor itself, providing direct service to thousands of customers across the province. This essay examines the two major events that brought Ontario Hydro into local distribution during this period: the creation of the Central Ontario System in 1916 and the Rural Power District in 1920. This essay draws on previously unexplored archival sources to argue that the two processes were quite separate from one another, and that only one – the Rural Power District – left a lasting institutional legacy in Ontario’s electricity sector. Both developments, however, reveal the “flexibility” of local political autonomy in Ontario – the cultural and political limits of appeals to local autonomy in the face of economic risk and opportunity and technological change.